2010
DOI: 10.2989/16073614.2010.488444
|View full text |Cite
|
Sign up to set email alerts
|

(Unoffi cial) Multilingualism in desegregated schools: Learners' use of and views towards African languages

Abstract: South Africa has a progressive Language in Education Policy (LiEP) advocating multilingualism, but the policy has been widely criticised for its lack of implementation. Notable is the hegemony of English in many schools, and in ex-Model C schools in particular. Some have argued that the choices of middle-class African parents in sending their children to English medium schools is threatening the survival of African languages and leading to language shift (De Klerk, 2000;Kamwangamalu, 2003a;2003b). Drawing on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Verhoef conducted a study among black teenagers in which it emerged that these youths perceived indigenous languages as vehicles for cultural inheritance, while English was more favourably viewed as having higher functional value. This view is supported by more recent studies which found that the youth still view their languages as inextricably linked to their culture, from which they derive a strong sense of self and identity, while English is perceived as an instrumental language (Ndlangamandla 2010;Rudwick 2004 and.…”
Section: Language Choice In Hiv and Aids Messages For Young South Afrmentioning
confidence: 77%
“…Verhoef conducted a study among black teenagers in which it emerged that these youths perceived indigenous languages as vehicles for cultural inheritance, while English was more favourably viewed as having higher functional value. This view is supported by more recent studies which found that the youth still view their languages as inextricably linked to their culture, from which they derive a strong sense of self and identity, while English is perceived as an instrumental language (Ndlangamandla 2010;Rudwick 2004 and.…”
Section: Language Choice In Hiv and Aids Messages For Young South Afrmentioning
confidence: 77%
“…offline conversation in the classroom and outside of the classroom space) (see Ndlangamandla, 2011). offline conversation in the classroom and outside of the classroom space) (see Ndlangamandla, 2011).…”
Section: English In a Linguistic Repertoirementioning
confidence: 99%
“…This is particularly true among users of African languages as home languages in urban communities (Slabbert and Finlayson 2000;Ndlangamandla 2010).…”
Section: Introductionmentioning
confidence: 95%
“…There are some studies that document the multilingualism of users of African languages (for example, Slabbert and Finlayson 2000;Ndlangamandla 2010) and in other studies the issue is treated conceptually (for example by Banda 2009;Prah 2010). However, the majority of the current studies about the multilingualism of South Africans focuses on the role of the home language and the potential influence of English related to issues of language maintenance and language shift; and it laments the failure of language policies that do not succeed in increasing the use of African languages in new and higher status domains.…”
Section: Introductionmentioning
confidence: 99%